Taxes and Income Inequality In Nigeria: Cointegration and Error Correction Mechanisms Evidence from 1980 – 2018: Array - Appah, Ebimobowei; Omesi, Israel (The Journal of Accounting and Management, 2021)
This study investigated the effects of taxes on income inequality in Nigeria for the period 1980 to 2018. The data for this research was obtained from the Central Bank of Nigeria, Federal Inland Revenue Service and National Bureau of Statistics. The data obtained were analysed using econometric methods such as augmented dickey fuller, cointegration and error correction mechanisms. The results revealed a significant negative relationship exists between personal income tax, company income tax and inequality; a negative but statistically insignificant relationship exist between value added tax and income inequality; a positive but statistically insignificant relationship exist between value added tax, government spending on education, government spending on health and income inequality. Hence the study concludes that taxes play a major role in income redistribution in Nigeria. The paper recommends amongst others that government should ensure compliance to tax payments because taxes provide a powerful policy tool effectively used for curing economic and social ills and should not to be set too high, as this would discourage investments and savings.